Calcium-activated chloride channel TMEM16A opens via pi-helical transition in transmembrane segment 4 - Andrei Y. Kostritskii; Yulia Kostritskaia; Natalia Dmitrieva; Tobias Stauber; Jan-Philipp Machtens (Proceedings of the National Academy of Sciences, 2025)
TMEM16A is a Ca 2+ -activated Cl − channel that has crucial roles in various physiological and pathological processes. However, the structure of the open state of the channel and the mechanism of Ca 2+ -induced pore opening have remained elusive. Using extensive molecular dynamics simulations, protein structure prediction, and patch-clamp electrophysiology, we demonstrate that TMEM16A opens a hydrated Cl − -conductive pore via a pi-helical transition in transmembrane segment 4 (TM4). We also describe a coupling mechanism that links pi-helical transition and pore opening to the Ca 2+ -induced conformational changes in TMEM16A. Furthermore, we designed a pi-helix-stabilizing mutation (I551P) that facilitates TMEM16A activation, revealing atomistic details of the ion-conduction mechanism. Finally, AlphaFold2 structure predictions revealed the importance of the pi helix in TM4 to structure–function relations in TMEM16 and the related OSCA/TMEM63 family, further highlighting the relevance of dynamic pi helices for gating in various ion channels.